Expanded Dengue Syndrome with Multiorgan Involvement in a Woman with Twin Intrauterine Fetal Death - A Case Report - Khanom, Taimoon Nahar (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Dengue is the most rapid mosquito-borne disease in the world. As per the WHO guidelines for dengue fever, a list of atypical or unusual manifestations, also termed ‘Expanded Dengue Syndrome’ (EDS), is mentioned. Pregnancy increases the risk of expanded dengue syndrome. A 32-year-old woman with IUFD (twin) at 36 weeks gestation with H/O 1 C/S was reported with expanded dengue syndrome with multiorgan involvement. She was referred to a tertiary centre with H/O high fever, loose emotion, less fetal movement, and dengue NS 1 antigen positive. She was eventually diagnosed as having expanded dengue syndrome with multiorgan involvement with IUFD (twin) at 36 weeks. The decision of LSCS was taken by a multidisciplinary approach. She was managed with FFP, platelet apheresis, therapeutic plasma exchange, and I/V antibiotics, in addition to liver & neurological support in the ICU unit. This case emphasised the hazards of dengue infection in pregnant women, which needs special consideration. Early recognition with careful monitoring and multidisciplinary management are the key factors in a favourable outcome for a dengue patient. J Bangladesh Coll Phys Surg 2023; 41: 105-108